Assessment of Uncertainties in Scenario Simulations of Biogeochemical Cycles in the Baltic Sea - Meier, H. E. Markus; Edman, Moa; Eilola, Kari; Placke, Manja; Neumann, Thomas; Andersson, Helén C.; Brunnabend, Sandra-Esther; Dieterich, Christian; Frauen, Claudia; Friedland, René; Gröger, Matthias; Gustafsson, Bo G.; et al. (Frontiers in Marine Science, 2019)
Following earlier regional assessment studies, such as the Assessment of Climate Change for the Baltic Sea Basin and the North Sea Region Climate Change Assessment, knowledge from available literature about future scenario simulations of biogeochemical cycles in the Baltic Sea and their uncertainties is assessed. Uncertainties in these projections are caused by climate model uncertainties (including global and regional models and the experimental setup), by unknown future nutrient load and greenhouse gas emissions (or concentrations) and by natural variability. The determination and reduction of uncertainties of scenario simulations are important issues for marine management. For instance, management would like to know from these coupled climate-environmental projections whether nutrient load abatement strategies such as the Baltic Sea Action Plan (BSAP) will meet its objectives of restored water quality status in future climate or whether additional measures are required. The results of an accompanied multi-model study indicate that the implementation of the BSAP will lead to a significant improvement of the environmental status of the Baltic Sea. However, uncertainties are large and their sources need to be understood to draw conclusions about the effectiveness of measures. Our assessment of sources of uncertainties in projections of biogeochemical cycles suggests that the biggest uncertainties (listed in descending order of importance) are caused by (1) unknown current and future bioavailable nutrient loads from land and atmosphere and the experimental setup (including the spin up strategy), (2) differences between the projections of global and regional climate models, in particular, with respect to the global mean sea level rise and regional water cycle, (3) differing model-specific responses of the simulated biogeochemical cycles to long-term changes in external nutrient loads and climate of the Baltic Sea region, and (4) unknown future greenhouse gas emissions. Regular assessments of the models’ skill (or quality compared to observations) for the Baltic Sea region and the spread in scenario simulations (differences among projected changes) and the improvement of dynamical downscaling methods are recommended.